2002
DOI: 10.2337/diabetes.51.6.1931
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Protects Nitric Oxide–Dependent Relaxation During Diabetes

Abstract: Interleukin (IL)-10, an anti-inflammatory cytokine, preserves endothelial function during acute inflammation. We tested the hypotheses that IL-10 plays a protective role in blood vessels during diabetes by suppressing impairment of endothelium-dependent relaxation and that protection by IL-10 is mediated by effects on superoxide (O 2 ؊ ). Streptozotocin (150 mg/kg i.p.) or citrate buffer was injected into IL-10 -deficient (IL-10 ؊/؊ ) mice and wild-type controls (IL-10 ؉/؉ ). In IL-10 ؉/؉ and IL-10 ؊/؊ mice, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
2
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 38 publications
3
61
2
1
Order By: Relevance
“…Consistent with previous studies (3,15,16,42), we have found that IL-10 plays a protective role in the alterations of vascular reactivity. Regional differences in cytokine-induced release and responsiveness to mediators appear to contribute to the dilator or constrictor responses observed in a specific vascular bed (42).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with previous studies (3,15,16,42), we have found that IL-10 plays a protective role in the alterations of vascular reactivity. Regional differences in cytokine-induced release and responsiveness to mediators appear to contribute to the dilator or constrictor responses observed in a specific vascular bed (42).…”
Section: Discussionsupporting
confidence: 81%
“…Exogenous IL-10 prevents proliferative vasculopathy by inhibiting inflammatory cell infiltration, smooth muscle cell proliferation, and chemokine expression (3,27). This cytokine counteracts the endothelial dysfunction induced by angiotensin II, lipopolysaccharide, and endothelin (ET)-1 (15,16,49,50). To promote changes in vascular reactivity, remodeling, inflammation, and oxidative stress, ET-1 activates MAPK signaling pathways, including ERK1/2 (7,19,21,48).…”
mentioning
confidence: 99%
“…A low production capacity of IL-10 has been found to be associated with the metabolic syndrome and type 2 diabetes 22 -24 . Experimental studies using gene-targeted mice 25 provide direct evidence that IL-10 offers some protection against endothelial dysfunction during diabetes and that this effect is mediated by inhibition of increased in superoxide anion in blood vessels. A reduced IL-10 serum level represents a marker of plaque instability favouring the development of acute coronary syndromes, and also indicative of a poor prognosis even after the occurrence of an acute ischaemic event caused by plaque instability 26 .…”
Section: Anti-inflammatory Cytokinesmentioning
confidence: 99%
“…By contrast, hypertension inhibited IL-10 and HO-1 expression, with a resultant increase in ALT to a level higher than that caused by the CDAA diet alone. In addition, indirect evidence indicates that IL-10 exerts a protective effect on endothelial function in diabetes and hypertension (17,30). IL-10 has also been shown to inhibit the activation of hepatic stellate cells and decrease hepatic fibrosis and apoptosis in a CCl4-induced rat liver fibrosis model (31,28).…”
Section: Cdaa Diet --------------------------------------------------mentioning
confidence: 99%